Lama Jambal Dorjo gegen and His Treatise “One who has Reached the Highest Wisdom” - I. G. Aktamov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the analysis of a historical source of the nineteenth century entitled “One who has reached the highest wisdom”, the authorship of which is attributed to the Mongolian lama, the hierarchy of the Buddhist Sangha, Jambal Dorjo gegen, who had the title “Nomun Khan”. It is emphasized that this source reveals some aspects of bilateral Russian-Mongolian diplomatic relations in the historical period that is very difficult for countries - the beginning of the 20th century, the period of civil wars and the formation of new statehood. The uniqueness of the source is determined by the fact that this manuscript was not the subject of historical analysis, its content reveals the position of theocratic Mongolia in relation to the Russian state. It is noted that the message of Jambal Dorjo gegen to his fellow believers-Buryats, already in the department of the Russian state, is seen as a kind of mandate, a wish for a safe and peaceful coexistence within the country. It is argued that the establishment of the state border between the Russian Empire and Mongolia has not yet passed its final phase, so its appeal to the Buryats, subjects of the White Tsar, fundamentally influenced the process of legitimization of imperial power in the territory of ethnic Buryatia.